Histone demethylase Lsd1 represses hematopoietic stem and progenitor cell signatures during blood cell maturation - Kerenyi, Marc A (eLife Sciences Publications, Ltd, 2013)
Here, we describe that lysine-specific demethylase 1 (Lsd1/KDM1a), which demethylates histone H3 on Lys4 or Lys9 (H3K4/K9), is an indispensible epigenetic governor of hematopoietic differentiation. Integrative genomic analysis, combining global occupancy of Lsd1, genome-wide analysis of its substrates H3K4 monomethylation and dimethylation, and gene expression profiling, reveals that Lsd1 represses hematopoietic stem and progenitor cell (HSPC) gene expression programs during hematopoietic differentiation. We found that Lsd1 acts at transcription start sites, as well as enhancer regions. Loss of Lsd1 was associated with increased H3K4me1 and H3K4me2 methylation on HSPC genes and gene derepression. Failure to fully silence HSPC genes compromised differentiation of hematopoietic stem cells as well as mature blood cell lineages. Collectively, our data indicate that Lsd1-mediated concurrent repression of enhancer and promoter activity of stem and progenitor cell genes is a pivotal epigenetic mechanism required for proper hematopoietic maturation. DOI: http://dx.doi.org/10.7554/eLife.00633.001